Dampak Dilakukannya Pengurangan Tenaga Kerja: Pengaruh Job Insecurity terhadap Kepuasan Kerja dengan Aspek Demografis sebagai Variabel Moderator - Yafet Eko Kurniawan; Tutuk Ari Arsanti (Universitas Proklamasi 45 Yogyakarta, 2017)
The objective of this study was to describe the effect of job insecurity on job satisfaction and demographic aspects as moderator variables. Demographics such as gender and age of past research showed that women have a higher job insecurity than men and also with age, the less employees feel a threat to their jobs. Quantitative methods through a survey used in this study. The results showed that job insecurity influence on job satisfaction, gender and age moderated the effect of job insecurity on job satisfaction.